Das 19. Jahrhundert - Mager, Inge (Arbeiten zur Kirchengeschichte Hamburgs, 2013)
The fourth part of Hamburg's church history in essays is dedicated to the 19th century.Considering the momentous upheavals and upheavals and the variety of important themes and formative figures, the texts reprinted or newly written here reflect only some of the events and developments relevant to Hamburg's church history in this eventful epoch.Irrespective of all possible additions, this volume offers numerous new and enlightening insights into the exciting urbanization process of a city and its churches on their path to modernity, marked by catastrophes and fortunes, reformist zeal and conservatism.